“It beats the hell out of going to a hospital”: service user experiences of telemedicine-based symptom-triggered alcohol withdrawal management - Nikki Bozinoff; Divya Prasad; Ke Bin Xiao; Anthony Ngoy; Bernard Le Foll; Anna Gordezky; Christian S. Hendershot; Sandra LaFleur; Lena C. Quilty; Victor M. Tang; Tara Marie Watson; Matthew E. Sloan (Addiction Science & Clinical Practice)
Abstract Introduction Increasingly, services for the management of substance use disorders have been developed or adapted for remote delivery. Limited research has investigated service user experience of these services. We undertook a qualitative sub-study, embedded within a pilot feasibility study of remote symptom-triggered alcohol withdrawal management, to better understand the experiences of participants. Our aim was to determine the acceptability of the intervention and refine intervention procedures. Methods Eligible participants were enrolled in the parent study and completed at least one day of telemedicine-delivered symptom-triggered alcohol withdrawal management. Individuals were adults with alcohol use disorder recruited using intensity sampling. Participants completed an audio-recorded, semi-structured interview. Thematic analysis was conducted using Braun and Clarke interpretive methodology. Results Fourteen individuals were enrolled in the study. Six themes were identified: benefits of being in the home environment, technological tensions, intervention-specific feedback, personal motivations for participation, post-program achievements and changes and navigating the ‘system’. Participants identified numerous benefits of being in the home environment including: increased comfort, privacy and security, normalizing abstinence in the home, flexibility to engage in other tasks, and the convenience of not travelling. Intervention-specific feedback included positive aspects of the intervention (interactions with staff, accountability, counselling, use of medication), areas for improvement (preparation, scheduling, medication logistics, and aftercare), and the meaning and role of having a support person available during treatment. Conclusion Participants found remote alcohol withdrawal management to be satisfactory and associated with several benefits including increased comfort, privacy, normalizing abstinence in the home, flexibility and convenience. They also provided important feedback for refinement of the intervention. Findings suggest that remote alcohol withdrawal management could play an important role in improving access to medical management of alcohol withdrawal, particularly in rural, remote or underserved areas.